Kinetic pH Titration to Predict the Acid and Hydrothermal Conditions for the Hydrolysis of Disaccharides: Use of a Microcapillary System - Toshinori Shimanouchi; Ryota Mano; Yu Yoshioka; Ayaka Fukuda; Kyung-Min Park; Yukitaka Kimura (Journal of Chemistry)
The hydrolysis of disaccharides was conducted using a microcapillary system under hydrothermal conditions (up to 190°C at 10 MPa and pH 4–11). The hydrolysis reaction showed a sigmoidal progression with time, especially under alkaline conditions. Analysis using a kinetic model yielded the reaction induction period. The specific pH value (pHamb) at the induction time, which is the pH value corresponding to the progression of disaccharide hydrolysis, was peculiar to each disaccharide. Finally, the calculation of the electron density around the oxygen atom of the glycosidic bond between saccharides was found to roughly predict the pHamb value required for the progression of hydrolysis.